RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO TURBIN CROSS-FLOW PADA SUNGAI AYUNG - Sega Awaludin; Putu Agus Arcana Surya; Cokordei Gedei Indra Partha; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2025)
The Cross Flow turbine is a type of turbine that utilizes hydraulic energy (water) from the Ayung River flow as its driving force and is very suitable for use in places with low head. Currently, the Cross Flow turbine is still very little used in Indonesia, especially in Bali. This is due to the difficulty of direct measurements by conducting tests related to influential parameters in the field. Therefore, it is necessary to. create a Micro. Hydro Power. Plant (MHP) with adequate terrain and water discharge and is not difficult to measure so as to obtain specific data. This study aims to create a design, determine the turbine specifications, analyze the torque, rotation speed, voltage, current, power, and, efficiency. generated from the MHP prototype with the Cross Flow turbine. The benefits of this study are also, expected. to be a referencei for further researchers to conduct research on MHP. The methods used in this study are, the library method, and the observation method. This study also discusses the analytical study of, the existing. hydropower potential, namely, the. water flow discharge and the height of the waterfall (head) of the Ayung River water flow. The turbine design calculation obtained an effective height of 6 meters with an inlet water velocity of 10.63 m/s and a circumferential velocity of 10.22 m/s indicating that the runner has an outer diameter of 0.15 meters, an inner diameter of 0.1 meters, a runner width of 0.1 meters, a distance between blades of 0.026 meters, a blade width of 0.025 meters, and a total of 18 blades. This prototype, test uses, a water flow, rate of 7 L or 0.007 opening, a guide vane angle of 30. The output produced in the no-load test obtained an average. turbine rotation results before being, coupled to a generator of 539 rpm, an average, turbine rotation results after being coupled of 415 rpm. The average result of the. largest turbine rotation under load is 504 rpm, the largest, generator rotation result under load is 306 rpm, the largest average generator, voltage. result is 9.64 volts, the, largest average. generator, current result, is 0.33 Ampere, thei largest. average, generator, power result is 3.23 Watts, the largest torque result is 0.07 Nm, the largest. PLTMH efficiency result is 6%.